Beyond Instructions: Exploring the Power of Directives in EFL Tutoring - Harmiyanti, Rizky; Yuliasri, Issy (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study explores the directive illocutionary acts produced by a tutor in a Small England Class during English teaching and learning. This research was conducted to find out the types of directive illocutionary acts employed, identifying the most and least frequent types and their implications. The data were analyzed by the descriptive qualitative method, and collected by recording the teaching and learning process, watching and listening to the video, transcribing the video, and classifying the tutor’s utterance into directive illocutionary acts. The writer applied Searle’s theory to the types of directive illocutionary acts which include direct, request, ask, urge, tell, require, demand, command, order, forbid, prohibit, enjoin, permit, suggest, insist, warn, advise, recommend, beg, supplicate, entreat, beseech, implore, and pray. The result of the study revealed that there are a total of 429 data points found in the speech, with command being the most dominant with a total of 247 (57.58%), followed by ask at 156 (36.36%), request at 12 (2.80%), suggest at 5 (1.17%), forbid at 3 (0.70%), recommend at 3 (0.70%) and the last three sequences (advise, tell, and urge) being the least dominant at 1 (0.23%). The findings indicate that commands were the most prevalent type of directive illocutionary acts, as they were mainly used to get the students to perform a specific action that the tutor desired i.e., translating the tutor’s speech into English when drilling session.